Amended description of the rarely reported bryophilous ascomycete Octospora svrcekii (Pyronemataceae) with notes on the phylogeny of the section Wrightoideae - Sochorová, Zuzana; Matočec, Neven; Kušan, Ivana; Janošík, Lukáš; Eckstein, Jan; Vega, Marcel; Mešić, Armin; Sedlářová, Michaela; Martínez-Gil, Rubén; Sochor, Michal (Phytotaxa, 2020)
The bryophilous ascomycete Octospora svrcekii, belonging to the section Wrightoideae, has so far been reported from only three localities in the world. New collections from Albania, Austria, Croatia, France, Slovakia and Spain have enabled a better understanding of its variability, ecology, distribution and phylogenetic relationships with other taxa within the section Wrightoideae. Octospora svrcekii was always found associated with Cratoneuron filicinum growing in constantly humid habitats (brooks, rivers or waterfalls), on calcareous bedrock. A species description based on both living and dead material is provided and compared with previous observations. A phylogenetic analysis of the section Wrightoideae, performed using the EF1α, SSU rDNA and LSU rDNA loci, revealed that Octospora svrcekii forms a monophyletic group with O. wrightii, O. erzbergeri, O. hygrohypnophila and O. americana, all of which are characterised by subglobose to broadly ellipsoid ascospores ornamented with isolated warts, and infect mosses in the order Hypnales, inducing galls on their rhizoids. Based on the molecular analysis, O. orthotrichi and O. affinis, formerly also considered as members of the section Wrightoideae, do not belong to the group.